Association of Serum Calcium and Magnesium Level with Febrile Seizure - Sarker, Aditi; Islam, Md Khairul; Pal, Nittyananda; Aman, Sakib; Sajib, Md Kamrul Hasan; Banu, Nazneen Akhter; Sultana, Naima (Sir Salimullah Medical College Journal, 2022)
Background: Febrile seizures occur in 2 to 5% of all children with a recurrence rate of 30 to 40%. Calcium and magnesium is closely related to pathophysiology of seizures and aim of this study was to find out the association of serum calcium and magnesium level with febrile seizure. Methods: A cross sectional analytical study was conducted among One hundred (100) subjects of both sexes with age range 6 months to 60 months in department of pediatrics from June 2019 to May 2020. The subjects were grouped into case (group A) and control (group B) by purposive sampling who were seeking fever with convulsion (group A) and fever without convulsion (group B). Statistical analyses were performed by Chi-square test and/or Fisher’s exact test as applicable for comparing qualitative variables and for quantitative variables using unpaired t-test and/or Mann-Whitney U test for comparing between the groups. Pearson’s Correlation Coefficient test was done to observe the correlation between low calcium and Magnesium level in febrile seizure. A p-value of <0.05 was considered as significant for all analytical tests. Results: Hypocalcaemia were more in 25-36 months of age and hypomagnesaemia 37-48 months in febrile seizure Hypomagnesaemia were more in patients who had previous febrile seizure (1.89 ± 0.73 mg/dl, p- value 0.045). Association and positive correlation were found between serum calcium and serum magnesium with febrile seizure. Multivariate logistic regression showed hypocalcaemia and hypomagnesaemia are independent risk factor for febrile seizures where hypocalcaemia OR=2.144 and hypomagnesaemia OR 1.2. Conclusion: Association and positive correlation were found between serum calcium and serum magnesium with febrile seizure and more in recurrent febrile seizure. Sir Salimullah Med Coll J 2022; 30: 14-22